TECHNOLOGIES FOR TEACHING GEOMETRIC CONSTRUCTION PROBLEMS IN PRIMARY CLASSES - Abdushukurova , Mashhura; Odiljonova , Ruxshona (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes technologies for teaching primary school students how to construct and work with geometric shapes. It examines innovative methods, visual and interactive approaches used in practical lessons, as well as opportunities for increasing students’ interest and developing their logical thinking skills. In addition, the article presents step-by-step approaches to solving geometric problems, methods for encouraging creative thinking, and ways of developing independent learning skills. The study provides useful recommendations for deepening mathematical competencies and effectively organizing mathematics education in primary grades.